Role of crystalline and damping anisotropy to the angular dependences of spin rectification effect in single crystal CoFe film. (16th September 2020) - Zeng, Fanlong; Shen, Xi; Li, Yi; Yuan, Zhe; Zhang, Wei; Wu, Yizheng
Abstract: The angular dependence of the microwave-driven spin rectification (SR) effect in single crystalline Co0.5 Fe0.5 alloy film is systematically investigated. Due to the strong current-orientation dependent anisotropic magnetoresistance (AMR), the SR effects in CoFe film strongly deviate from the ordinary sin 2 φ M cos φ M relation with φ M defined as the magnetization angle away from the current. A giant Gilbert damping anisotropy in the CoFe film with a maximum–minimum ratio of 520% is observed, which can impose a strong anisotropy onto magnetic susceptibility. The observed unusual angular dependence can be well explained by the theory including current-orientation dependent AMR and anisotropic magnetic susceptibility. Our work also suggests that the strong current-orientation dependent AMR in single crystalline CoFe film could exist up to the gigahertz frequency range.